CALLUS INDUCTION FROM BRANCHES OF KAPPAPHYCUS STRIATUS UNDER DIFFERENT CULTURE CONDITIONS - Mo, Vu Thi; Huynh, Tran Van; Nghia, Le Trong; Tung, Hoang Thanh; Lam, Nguyen Ngoc; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2018)
Kappaphycus striatus is growing in some central coastal provinces as a source of carrageenan extract. It is mainly propagated in the form of vegetative reproduction and sporulation. However, this method still has some limitations. At present, there is no report on the micropropagation of this species through callus induction. In this study, effect of plant growth regulators (PGRs) (Naphthalene acetic acid [NAA] and 6-bezyl amino purine [BAP]), intensity of light and concentration of agar on callus induction derived from branches of Kappaphycus striatus maintaned in laboratory for 1 month were tested. After 2 month culture, the results showed that branches of Kappaphycus striatus cultured on PES (Provasoli enriched seawater) medium (without PGRs) gave the best callus induction rate (75.7%) and survival rate (77.3%) compared to those on PES medium supplemented PGRs. The optimal conditions for callus induction were PES solidified medium supplemented with 1.5 – 2.0% agar in 5 µmol.m-2.s-1 of light intensities. Callus induction rates (66.7% – 67%), survival rate (63.7% – 64.3%) of explants from branches incubating on PES medium with 1.5 – 2.0% agar were higher than differrent agar concentrations. Callus induction rates (67%), survival rate (77.7%) of explants from branches incubating on PES medium under 5 µmol.m-2.s-1 were higher than differrent light intensities. The results showed that there were three different types of calluses observed namely white filamentous callus, brown filamentous callus and compact callus. These calli that were big and had filamentous type, will be a good material for the next production stage of embryonic callus production and seedling regeneration from micropropagules.